Evaluation and modelling of the lithium fluoride based thermoluminescent detector response at the CERN-EU high-energy reference field (CERF). (March 2023) - Van Hoey, Olivier; De Saint-Hubert, Marijke; Parisi, Alessio; Caballero-Pacheco, Miguel Ángel; Domingo, Carles; Pozzi, Fabio; Froeschl, Robert; Stolarczyk, Liliana; Olko, Pawel
Abstract: Lithium fluoride (LiF) thermoluminescent detectors (TLDs) are commonly used for measurements in mixed high energy radiation fields such as space, hadron radiotherapy and other high energy accelerator facilities. However, the results of these measurements are often challenging to interpret since the radiation field compositions are not known a priori. The goal of this work was to model and understand the LiF TLD response in the CERN-EU high-energy Reference Field (CERF). Six different LiF TLD types, namely MTS (LiF:Mg, Ti) and MCP (LiF:Mg, Cu, P) TLDs with different Li abundances, were irradiated at CERF. For the modelling of their response, CERF reference fluence energy spectra from FLUKA simulations and TLD relative luminescence efficiencies according to the Microdosimetric d(z) Model were collected from previous works and supplemented with new relative luminescence efficiency calculations for neutrons with energies above 0.01 MeV. Dedicated MCNP6.2 simulations were performed to obtain the required fluence to absorbed dose conversion factors. Results demonstrated that the response of LiF detectors can be well predicted even for complicated, mixed radiation fields. The modelling allowed to assess the dose contributions from different radiation types in mixed fields. Based on the results of this work, a methodology was proposed to perform LiF TLD measurements in well-characterized mixed fields in terms of absorbed dose in water or tissue. In unknown mixed radiation fields MTS-7 TLDs are recommended to assess the non-neutron component of the absorbed dose in water or tissue. Assessing the dose from neutrons requires dedicated neutron detectors. Highlights: Six different LiF TLD types were used for dose assessment at CERF. The response of these TLDs and the contributions from different radiation types were modelled in detail. Measured and modelled doses were in good agreement with each other. Recommendations were given for LiF TLD measurements in mixed radiation fields such as hadron therapy and space.